A comprehensive stress model for gas-particle flows in dense and dilute regimes. (23rd November 2020) - Zhao, Junnan; Liu, Guodong; Li, Wei; Yin, Xiaolong; Wu, Yao; Wang, Chunlei; Lu, Huilin
Highlights: A comprehensive solid stress model for gas-particle flows is proposed. It can give an accurate prediction of bubble size, bubble shape and detachment time. Specific threshold of solid fraction in previous frictional stress models is avoided. Abstract: A comprehensive solid stress model including the whole flow regimes for gas-particle flows is proposed. In the inertial regime characterized by low solid concentrations, solid stress is closed by kinetic theory based on particle collision mechanisms. In the quasi-static regime characterized by high particle concentrations, solid stress is closed by the frictional stress model based on soil mechanics. In the intermediate regime, solid stress is closed by an inertial number model without the need to specify a threshold of particle concentration for the transition. This new model is validated with experimental data from bubbling fluidized beds with a central jet, and compared with simulation results predicted by kinetic theories. Results show that this new model can give a more accurate prediction of bubble size, bubble shape and detachment time than through kinetic theory or other previous models. The problem of specifying a threshold value when employing previous models is solved.